Improving the Professional Ethics of Facilitators through Andragogical Methodologies for Non-Formal Education Delivery in Nigeria - Adebola, Helen. E.; Ewelum, J.N.; Madu, C.O. (Advances in Social Sciences Research Journal, 2016)
There are professional ethics that guide people in any profession. Hence, people are expected to perform credibly well in their different professions. Therefore, this paper examines some ways of improving the professional ethics of facilitators through andragogical methodologies for non-formal education delivery in Nigeria. The paper also discusses some of the andragogical methods that facilitators can use in teaching and learning situation which can improve the professionalization of facilitators. The paper concludes with an urgent call for the need to improve the professional ethics of facilitators in all non-formal education settings and service delivery. Based on the background of the study, some recommendations are made that facilitators teaching in non-formal education should be trained, certified and grounded in adult education methodologies before they are allowed to teach adult learners by the Agency for Adult and Non-formal Education. The facilitators teaching in non-formal education should be full-time facilitators and not part-time facilitators. Seminars, workshops and conferences should be organized from time to time by the agency for adult and non-formal education for facilitators in order to share experiences and ideas for the improvement of adult education.